Joint Survey Processing. III. Compact Oddballs in the COSMOS Field—Little Red Dots and Transients - Yu-Heng Lin; Andreas L. Faisst; Ranga-Ram Chary; Anton M. Koekemoer; Joseph Masiero; Daniel Masters; Vihang Mehta; Harry I. Teplitz; Gregory L. Walth; John R. Weaver (The Astrophysical Journal)
We present the Hubble Space Telescope (HST) Advanced Camera for Surveys (ACS) G800L grism spectroscopy observation of the faint active galactic nuclei (AGN) candidates in the Cosmic Evolution Survey field at redshift of 6 selected by the point-source morphology and the photometry drop-off at 8000 Å. Among the sample of seven objects, only one is detected by multiple bands and has a similar shape of spectral energy distribution as the so-called “little red dots” of James Webb Space Telescope (JWST)–selected AGN candidates, but our object is 3 mag brighter than the JWST sample. We draw the upper limit of the AGN luminosity function Φ = 1.1 × 10 ^−7 Mpc ^3 mag ^−1 for M _UV = −21 at redshift of 6. The rest of the sample shows inconsistent flux density when comparing magnitudes of HST ACS F814W to the Subaru i -band and z -band magnitudes combined. The HST ACS G800L grism observation shows that this inconsistency cannot be created from an emission line. Therefore, we speculate that these objects are transients with the light-curve decay timescale of at most 6 yr in the observed frame.